Pengembangan Booklet Berbantuan Video Animasi dengan Memanfaatkan QR Code pada Submateri Isomer Konstitusional - Nurzam Indah Utami; Rahmat Rasmawan; Ira Lestari; Rini Muharini; Maria Ulfah (Postgraduate, University of Mataram, 2024)
This research aims to produce a product in the form of a booklet assisted by an animated video by utilizing QR codes on constitutional isomers sub-material to increase student understanding and reduce misconceptions on constitutional isomers. This research method is research and development (R&D) with a 4D development model consisting of the Define, Design, Develop and Disseminate stages. However, this research only reached the Develop stage. The validation data was analyzed using Content Validity Ratio (CVR) and Content Validity Index (CVI), while the student response questionnaire to the product was measured using a Likert scale. The results of product validation from every aspect, both in booklets and animated videos, obtained a CVI value of 0.99 and were declared valid and suitable for use as learning media. Students also gave good responses, which was shown in the initial response test with a percentage of 85% in the good category and in the main response test with a percentage of 84% in the good category.